Pengembangan Bisnis Ayam Broiler Berbasis Industri 4.0 - Ikhwana, Andri; Taptajani, Dedi Sa'dudin; Prilangga, Regi (Jurnal Kalibrasi, 2025)
Using Industry 4.0-based technology, this research aims to improve the efficiency of broiler feeding. The automated feeding system developed is capable of regulating the schedule and amount of feed with great accuracy and enables remote monitoring through the Internet of Things (IoT). The results show that, when compared to manual methods, this technology can increase productivity by up to 20%, reduce operational costs, and accelerate the payback time of investment by up to 27%. With these findings, there is a great opportunity to increase competition in Indonesian broiler farming.